Absorption enhancement of aged black carbon aerosols affected by their microphysics: A numerical investigation. (November 2017) - Zhang, Xiaolin; Mao, Mao; Yin, Yan; Wang, Bin
Highlights: The importance of coating microphysics on BC absorption enhancement is stressed. Absorption enhancement of aged BC is numerically studied with recent observations. Sensitivities of coated BC absorption enhancement are numerically investigated. The microphysical factors affecting BC lensing effect are addressed. More coating enhance lensing effect further unless BC near heavily coating boundary. Abstract: An idealized spherical model with black carbon (BC) aggregates fully coated by sulfate is developed to study the absorption enhancement ( Eab ) of polydisperse BC aerosols, which is numerically calculated by the multiple-sphere T-matrix method (MSTM). The aim of this study is to evaluate the effects of aerosol microphysics on the absorption enhancement of fully coated BC particles. The Eab values of accumulation concentric coated BC aggregates with different BC fractal dimensions vary within 2%, while those of coarse coated BC aggregates can alter up to 20% depending on shell-core ratio Dp / Dc (spherical equivalent particle diameter divided by BC core diameter). The BC position inside coating can result in an Eab decrease of fully coated BC aggregates up to approximately 15% and 20% in the accumulation and coarse modes, respectively. Compared with the concentric spherical structure, the off-center coated BC aggregates shows similar Eab with a difference less than 9% in the accumulation mode, whereas it can lead to up to 31% reductions in Eab in the coarse mode. The absorption enhancement of aged BC is sensitive to particle size distribution, and it decreases as particles becomes larger in accumulation mode, whereas the reverse is true in coarse mode. For BC aggregates fully coated with a very thin layer sulfate at different size distributions, Eab values are generally in ranges of 1.5–1.8 and 1.3–1.4 in accumulation and coarse modes, respectively, while with coating reaching Dp / Dc  = 2.7, their values range from 1.7–2.4 and 2.0–2.1 in accumulation and coarse modes, respectively. Our study indicates that, larger Dp / Dc with BC aggregates not close to the coating boundary, or BC position closer to particle geometric center enhance BC lensing effect, whereas BC aggregates near the boundary of heavy coating may not further enhance lensing effect significantly with increased coating fraction.